Hubungan Obesitas Terhadap Insomnia - Sintia Ema Rahma; Olga Melina Evania; Retta Rikah Elfrida (Lembaga Pengembangan Kinerja Dosen, 2023)
Explores the relationship between obesity and insomnia, two prevalent and growing health concerns in today's society. Research has shown that there is a bidirectional relationship between these two conditions, with each contributing to the development and exacerbation of the other. The paper examines the various mechanisms that link obesity and insomnia, such as hormonal imbalances, inflammation, and sleep-disordered breathing. Additionally, the paper discusses the implications of this relationship on public health, as well as potential interventions for preventing and treating both conditions. By understanding the complex interplay between obesity and insomnia, healthcare providers and policymakers can better address these important health issues and improve patient outcomes.